Biodiversity of hard coral (Scleractinia) and relation to environmental factors turbid waters in Spermonde Islands, South Sulawesi, Indonesia - DEDI PARENDEN; JAMALUDDIN JOMPA; CHAIR RANI; WILLEM RENEMA; JEREMIAS RUMALA TUHUMENA (Society for Indonesian Biodiversity, 2023)
Abstract. Parenden D, Jompa J, Rani C, Renema W, Tuhumena JR. 2023. Biodiversity of hard coral (Scleractinia) and relation to environmental factors turbid waters in Spermonde Island, South Sulawesi, Indonesia s. Biodiversitas 24: 4521-4529. Water turbidity has an impact on coral growth and the diversity of coral species in the waters. Calculation of coral cover, coral diversity and environmental parameters need to be done to determine the effect of environmental parameters on growth. This research was conducted in July 2020-February 2021 in the Spermonde Islands, South Sulawesi, Indonesia, which focused on the inner zone area with high turbidity levels. The research was conducted at four observation locations, namely Kayangan Island, Samalona Island, Gusung Tallang and Lae-Lae Island. Primary data in the form of coral cover using the Underwater Photo Transect method, diversity data using the quadrant transect method and environmental parameters measured in-situ and ex-situ. The results of this study showed (1) the percentage of coral cover at each research location was classified as poor because it was in the range of 3-15%, (2) coral diversity on Samalona Island was classified as high (H'=3.2) while on Kayangan Island, Laelae Island and Gusung Tallang was classified as medium with values ranging from 2.21-2.83; and (3) environmental parameters such as turbidity, Total Suspended Solid (TSS), Total Dissolved Solid (TDS), nitrate, and phosphate and based on the results of regression analysis has a negative effect on coral cover, while turbidity and Total Suspended Solid (TSS) parameters have a significant effect on coral cover (p<0.05). These results have the potential to determine the composition of hard corals (Acropora sp.) in turbid areas and potentially serve as transplant fragments to mitigate coral damage.